A practical approach to communicating benefit-risk decisions of medicines to stakeholders - Leong, James; Walker, Stuart; Salek, Sam (Frontiers in Pharmacology, 2015)
Abstract Purpose The importance of a framework for a systematic structured assessment of the benefits and risks has been established, but in addition, it is necessary that the benefit-risk decisions and the processes to derive those decisions are documented and communicated to various stakeholders for accountability. Hence there is now a need to find appropriate tools to enhance communication in a manner that would uphold transparency, consistency and standards. Methods A retrospective, non-comparative study was conducted to determine the applicability and practicality of a summary template in documenting benefit-risk assessment and communicating benefit-risk balance and conclusions for reviewers to other stakeholders. The benefit-risk (BR) Summary Template and its User Manual was evaluated by 12 reviewers within a regulatory agency in Singapore, the Health Sciences Authority (HSA). Results The BR Summary Template was found to be adequate in documenting benefits, risks, relevant summaries and conclusions, while the User Manual was useful in guiding the reviewer in completing the template. The BR Summary Template was also considered a useful tool for communicating benefit-risk decisions to a variety of stakeholders. Conclusions The use of a template may be of value for the communicating benefit-risk assessment of medicines to stakeholders.